Preliminary Study of Antibiotics Susceptibility Testing and Pathogens Associated with Nosocomial Infections in a Tertiary Hospital - Tolou-Ghamari, Zahra (Anti-Infective Agents, 2024)
Background: Health care associated with multiresistant pathogens is rising globally. As nosocomial infections (NIs) could increase hospital stay, morbidity, mortality and disability, therefore the aim of this preliminary study was to define antibiotics and pathogens associated with NIs in a main tertiary hospital in Isfahan, Iran. Methods: The data were extracted from the official database of hospital NIs records. For each patient, the reported infections were abbreviated as: UTI-SUTI, VAE-PVAP, BSI-LCBI, SSIDIP and so on. For continuous variables, mean ± standard deviation, and for categorical variables, frequency was used. Results: The study population was 5542 patients, comprised of males (n = 3282) and females (n = 2260). With a minimum of 15 and a maximum of 99, the mean age in 5313 patients was 58.5 ± 19.1 years old. The highest reported NIs (n = 77%) were associated with the ages between 30- 80 years old. Sites of NIs in 93% were as: VAE-PVAP- VAE-IVAC; 31%, UTI-SUTI; 30%, SSI-DIP; 19%, BSI-LCBI; 13%, and other individual infection (7%) with the main pathogens associated with Acinetobacter baumannii, Klebsiella pneumonia, Candida and Staphylococcus spp. Antibiotic susceptibilty testing showed the most sensitivity of isolates against Vancomycin (62%), Gentamicin (59%), Ampicillin (44%), Amikacin (35%) and Co-trimoxazol (32%). Conclusion: As most NIs are avoidable, for commissioning an efficient surveillance system, further study of pathogens in relation to evidence-based antibiotic-therapy and advanced infection control program is suggested to be valuable.
Keywords: bloodstream